Endophytic ancestors of modern leaf miners may have evolved in the Late Carboniferous - Knecht, Richard J (The New phytologist, 2023)
© 2023 The Authors. New Phytologist © 2023 New Phytologist Foundation This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA.